Pilot study on prevalence of enamel erosion in patients having gastroesophageal reflux disease (GERD) attending IIUM dental clinic - Ahmad Tajudin, Ahmad Nur Hilmi; Aminuddin, Aiman Za'im; Alfarisi, Hamad; Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Md Jalil, Muhammad Ateeq (University of Malaya, 2025)
Gastroesophageal reflux disease (GERD) is a common digestive disorder that affects millions of people worldwide. Reflux of gastric acid may cause oral acidification that can induce teeth demineralization. Destruction of dental hard tissue by acid reflux necessitates a combine approach involving medical and dental profession. This pilot study aims to assess association between enamel erosion and GERD, and estimate prevalence of enamel erosion among GERD patients. A total of 22 patients (GERD and control) were involved in this case-control study. Dental charting was done using five-point ordinal scales of modified Tooth Wear Evaluation System (TWES 2.0). Cohen’s Kappa Coefficient was used for assessment of intra-rater and inter-rater reliability. Fisher’s Exact Test was used to determine association between enamel erosion and GERD, reflecting prevalence. Out of 11 GERD patients, 63.6% exhibit enamel erosion, whereas only 9.1% of control patient presented with enamel erosion. Fisher’s Exact Test showed a significant prevalence of enamel erosion in GERD patients (p=0.024). This study showed a clear association between enamel erosion and GERD, and it can be considered as an oral manifestation in patient with GERD. Future study involving large sample size is recommended to show clear statistical evidence of association between enamel erosion and GERD.